Role of Shwasakuthar Rasa and Other Herbomineral Formulations with Yoga in Migraine - Sapna; Rashmisnata dash; Sujeet kumar (AYUSHDHARA, 2024)
Ayurveda is an ancient traditional system of medicine to treat illness and encourage well being by using natural whole body healing techniques. Migraine is a primary headache disorder which is characterized by episodic recurrent attacks. As it affects one billion individuals each year across the worldwide has proven to one of the most common neurological disorders with high prevalence and morbidity among the younger age groups. Migraine can be classified on the basis of presence of Aura which shows prodromal symptoms like irritability, behavioural changes, etc and associated symptoms of photophobia, phonophobia and vomiting that usually lasts for 4 to 72 hours. In Ayurveda, migraine is clinically correlated with Ardhavabhedaka which is described as Tridoshapradhana by Sushruta and Vatakaphapradhana by Vagabhata. The management of migraine is done routinely by reducing the symptoms and the episodic recurrent attacks with Ayurvedic approach as modern medicine cause gastric irritation and drug dependency which further triggers the attack. The present case of 35 years old female diagnosed with migraine has shown symptoms of headache involving left side of head associated with nausea, vomiting and sensitivity to light and sound. The patient was treated with Nasya Karma which act as a gateway to head as said by Acharya Charaka and with oral Ayurvedic herbomineral formulation Shamana Chikitsa was done that alleviates the symptoms of Ardhavabhedaka. A significant relief from all symptoms was observed within a period of 15 days, demonstrating the Ayurveda as the best way to improve the overall well being of mind, body and spirit.